Enhancing Teachers' Digital competency through Participatory LMS Training for Junior High School Teachers - Abdul Rahman; Brezto Asagi Dewantara; Lazaro Kumala Dewi (Universitas Sebelas Maret, 2026)
The digital competency gap among teachers is a crucial barrier to integrating technology into learning and represents a real challenge for junior high school teachers, as technology proficiency remains uneven. This study aimed to examine the effectiveness of a participatory Learning Management System (LMS) training program designed to improve the digital competency of 28 teachers at State Junior High School (SMPN 24) in Banjarmasin City. This study used a one-group pre-test–post-test design. The Shapiro–Wilk normality test confirmed that the data were normally distributed (p > 0.05); therefore, a paired samples t-test was used to measure the impact of the intervention. The results showed a highly significant increase in teacher competency scores from before the training (mean = 75.00, SD = 13.264) to after the training (mean = 89.82, SD = 7.134), with a p-value (p < 0.001), indicating a statistically significant improvement in teachers’ digital competency after participating in the LMS training program. These findings demonstrate that a participatory training approach effectively improves teachers’ digital competency and can serve as a strategic model for professional development in the digital era.